Preponderance of CTLA4 Variation Associated With Autosomal Dominant Immune Dysregulation in the MYPPPY Motif - Siggs, Owen M.; Russell, Amanda; Singh-Grewal, Davinder; Wong, Melanie; Chan, Pearl; Craig, Maria E.; O'Loughlin, Ted; Stormon, Michael; Goodnow, Christopher C. (Frontiers in Immunology, 2019)
One of the primary targets of immune checkpoint inhibition is the negative immune regulatory molecule CTLA-4. Immune-related adverse events are commonly observed following CTLA-4 inhibition in melanoma treatment, and a spectrum of these conditions are also observed in individuals with germline haploinsufficiency of CTLA4. Here we describe a heterozygous de novo missense variant of CTLA4 in a young girl with childhood-onset autoimmune hepatitis and polyarthritis, the latter responding to treatment with CTLA-4-Ig fusion protein. This variant lay within the highly conserved MYPPPY motif of CTLA-4: a critical structural determinant of ligand binding, which is also bound by the anti-CTLA-4 monoclonal antibody ipilimumab. Within the spectrum of CTLA4 variants reported, missense variants in the MYPPPY motif were overrepresented when compared to variants within a control population, highlighting the physiological importance of this motif in both the genetic and pharmacological regulation of autoimmunity and anti-tumour immunity.